Unexpected increase in structural integrity caused by thermally induced dwarfism in large benthic foraminifera - Danna Titelboim; Nikita J. Rothwell; Oliver T. Lord; Robert L. Harniman; Leanne A. Melbourne; Daniela N. Schmidt (Royal Society Open Science, 2024)
Climate change is predicted to negatively impact calcification and change the structural integrity of biogenic carbonates, influencing their protective function. We assess the impacts of warming on the morphology and crystallography of Amphistegina lobifera, an abundant benthic foraminifera species in shallow environments. Specimens from a thermally disturbed field area, mimicking future warming, are about 50% smaller compared with a control location. Differences in the position of the ν1 Raman mode of shells between the sites, which serves as a proxy for Mg content and calcification temperature, indicate that calcification is negatively impacted when temperatures are below the thermal range facilitating calcification. To test the impact of thermal stress on the Young's modulus of calcite which contributes to structural integrity, we quantify elasticity changes in large benthic foraminifera by applying atomic force microscopy to a different genus, Operculina ammonoides, cultured under optimal and high temperatures. Building on these observations of size and the sensitivity analysis for temperature-induced change in elasticity, we used finite element analysis to show that structural integrity is increased with reduced size and is largely insensitive to calcite elasticity. Our results indicate that warming-induced dwarfism creates shells that are more resistant to fracture because they are smaller.